The effect of oral curcumin on vincristine-induced neuropathy in pediatric acute lymphoblastic leukemia: A double-blind randomized controlled clinical trial - Eghbali, Aziz; Adibifar, Mahsa; Ghasemi, Ali; Afzal, Roghayeh Rahimi; Moradi, Katayoun; Eghbali, Aygin; Faress, Foroozan; Ghaffari, Kazem (BMC cancer, 2025)
Background Peripheral neuropathy is a major adverse effect of Vincristine (VCR) in pediatric acute lymphoblastic leukemia (ALL) patients. Curcumin can prevent the development of many neurological diseases. Method This clinical trial study was conducted on 141 pediatric ALL patients, all over 5 years old. The subjects were randomly divided into a curcumin-treatment group and a placebo group. In the curcumin-treatment group, patients received 3 mg/kg oral curcumin capsules twice a day for 3 months. In the placebo cohort, participants were administered placebo capsules twice a day for 3 months. Administration of VCR was started in all patients in both groups, with a weekly dose of 1.5 mg/m 2 . Result Overall, 39.4% of participants in the curcumin treatment group and 70.0% in the placebo group had VIPN. Thus, a significant difference in the incidence of VIPN was observed in the two groups ( P < 0.001). A significantly higher frequency of motor nerve abnormalities in all types of nerves was observed in the placebo group than in the curcumin treatment group ( P < 0.05). Conclusions The results of our study showed that curcumin is effective in preventing the development of VIPN and leads to the improvement of VIPN in these patients. Our findings indicate that the prevalence of VIPN was substantially lower in the curcumin-treated group compared to the placebo group, as confirmed by both NCS and EMG assessments. Furthermore, curcumin demonstrated a protective effect against motor and sensory nerve damage, with a significant reduction in motor nerve abnormalities. Trial registration This study was registered at https://irct.behdasht.gov.ir/trial/73161 . Trial registration number: IRCT20201107049296N3. Date of registration: 2022-09-11.